2017
DOI: 10.1111/cei.13048
|View full text |Cite
|
Sign up to set email alerts
|

DC-SIGN reacts with TLR-4 and regulates inflammatory cytokine expression via NF-κB activation in renal tubular epithelial cells during acute renal injury

Abstract: In the pathological process of acute kidney injury (AKI), innate immune receptors are essential in inflammatory response modulation; however, the precise molecular mechanisms are still unclear. Our study sought to demonstrate the inflammatory response mechanisms in renal tubular epithelial cells via Toll-like receptor-4 (TLR-4) and dendritic cell-specific intercellular adhesion molecule 3-grabbing non-integrin 1 (DC-SIGN) signalling. We found that DC-SIGN exhibited strong expression in renal tubular epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Damage-associated molecular patterns can be transferred into renal tubular epithelial cells trough EVs (138) and prevent tubular recovery (139,140). Pathogen-associated molecular patterns, such as LPS, upregulate the expression of DC-SIGN and toll-like receptor 4, stimulating tubular secretion of IL-6 and TNFα (141).…”
Section: Renal Tubular Epithelial Cellsmentioning
confidence: 99%
“…Damage-associated molecular patterns can be transferred into renal tubular epithelial cells trough EVs (138) and prevent tubular recovery (139,140). Pathogen-associated molecular patterns, such as LPS, upregulate the expression of DC-SIGN and toll-like receptor 4, stimulating tubular secretion of IL-6 and TNFα (141).…”
Section: Renal Tubular Epithelial Cellsmentioning
confidence: 99%
“…Moreover, many pathogens are capable of diverting the system to inhibit or modulate the immune response using these pathways [61]. Engagement of DC-SIGN by pathogens with mannose structures, like Candida albicans, human immunodeficiency virus-1, and M. tuberculosis, modulates TLR4 [62] and TLR2 signaling pathways in particular. M. tuberculosis and M. bovis are also able to produce mannose-capped lipoarabinomannan (ManLAM), a glycolipid targeting DC-SIGN that interferes with TLR2 signaling, thereby inducing IL-10 secretion by DCs [62,63].…”
Section: Pathogen-induced Immune Tolerancementioning
confidence: 99%
“…Engagement of DC-SIGN by pathogens with mannose structures, like Candida albicans, human immunodeficiency virus-1, and M. tuberculosis, modulates TLR4 [62] and TLR2 signaling pathways in particular. M. tuberculosis and M. bovis are also able to produce mannose-capped lipoarabinomannan (ManLAM), a glycolipid targeting DC-SIGN that interferes with TLR2 signaling, thereby inducing IL-10 secretion by DCs [62,63]. In this context, DC-SIGN activation by ManLAM also modulates the TLR4-mediated NFκB signaling pathway and modifies the IL-10/IL-12p70 secretion balance in favor of IL-10 to promote the infection.…”
Section: Pathogen-induced Immune Tolerancementioning
confidence: 99%
“…Among these factors, the early inflammation responses in kidneys are increasingly recognized as a major mechanism of sepsis-induced AKI. Previous studies have indicated that endotoxins, such as lipopolysaccharide (LPS), bind to Toll-like receptor 4 (TLR4), leading to the activation of the NF- κ B pathway in septic AKI, and these processes are initiated a few hours with the production of cytokines, such as TNF-a and IL-1, and the infiltration and activation of immune cells [ 8 , 9 ]. Castoldi et al reported that TLR2, TLR4, and MyD88 mRNAs are highly expressed in the renal tissue after sepsis.…”
Section: Introductionmentioning
confidence: 99%